The mediation of trust in principals between the effect of school-based management on school effectiveness in Oman - Hussein Amzat, Ismail; Alabri, Khalaf Marhoun; Hamad, Omer; Al-Ani, Wajeha Thabet Khadem (Emerald Publishing, 2025)
This article investigates the direct effect of SBM factors on school effectiveness (SE) and the mediating effect of trust between SBM and SE.